DIFFERENTIATING HOLIDAY ALLOWANCE TAX REGULATIONS FOR PRIVATE AND CIVIL SERVANTS - Siti Nur Wijayanti; Idul Hanzah Alid (Fakultas Hukum Universitas Komputer Indonesia, 2026)
Study This discusses the arrangement of juridical Income Tax (PPh) deductions on Holiday Allowance (THR), as well as analyzing the justice and equality law on the difference in tax treatment between the employee sector, the private sector, and civil servants (ASN). Background study. This is based on the existence of different mechanisms of taxation for THR: employees are privately charged, cutting Income Tax in general, while for ASN, THR is taxed by the government through the Government-Paid Tax (DTP) scheme. Research this aim: for the study's arrangement, analyze the laws governing the mechanism and their suitability with the principles of justice in law, taxation, equality in law, and public administration. Research This uses a methodological approach to jurisprudential norms, with an emphasis on legislation and conceptual analysis of taxation regulations, doctrine, and relevant scientific literature. show that, in a way, normative cutting Income Tax on THR for employee private sector and permanent civil servants is, within the framework law, the same taxation. Still, there is a difference in the mechanism for guaranteeing the tax burden. The difference is part of the policy of fiscal government, but it can potentially spark debate over the implementation principle of horizontal justice in the tax system. Therefore, an evaluation of the policy taxation related to THR is required to ensure that the system of taxation continues to reflect the principles of justice, equality, and certainty in the policy state's fiscal policy.